2007
DOI: 10.1080/03601230701229114
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of bensulfuron-methyl in an agricultural alkaline soil

Abstract: A field experiment to determine the available bensulfuron-methyl (BSM) in the upper soil layer was conducted in an agricultural area in the South of Spain. To facilitate herbicide analysis, two application rates were employed, 200 g ha(-1) and 5 kg ha(-1). Samples of upper soil and soil solution were collected. Soil solution was sampled by means of metallic samplers, placed at a depth of 35 cm. In the plots receiving the lower dose ceramic suction, porous cups were also installed. Results from soil solution sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
7
0
3
Order By: Relevance
“…However, the difference was not significant when comparing the value in the first-phase aerobic degradation with that of anaerobic degradation of bensulfuron-methyl. Previous studies have also shown that there was an overlap between the ranges of aerobic and anaerobic half-lives of bensulfuron-methyl (Berger and Wolfe 1996;Delgado-Moreno et al 2007). The difference was clearer for imazosulfuron, which is a chlorinated compound because reductive dehalogenation is thermodynamically favorable under reduced conditions (Smidt and de Vos 2004).…”
Section: Anaerobic Soil Degradationmentioning
confidence: 88%
“…However, the difference was not significant when comparing the value in the first-phase aerobic degradation with that of anaerobic degradation of bensulfuron-methyl. Previous studies have also shown that there was an overlap between the ranges of aerobic and anaerobic half-lives of bensulfuron-methyl (Berger and Wolfe 1996;Delgado-Moreno et al 2007). The difference was clearer for imazosulfuron, which is a chlorinated compound because reductive dehalogenation is thermodynamically favorable under reduced conditions (Smidt and de Vos 2004).…”
Section: Anaerobic Soil Degradationmentioning
confidence: 88%
“…It was reported that the herbicide was immobile to moderately mobile in soils and easy to be adsorbed by soil particles 68 . As BSM is a kind of soil-applied herbicide, the adsorption behavior has significant effect on its bioavailability, as well as on environmental fate 9,10 . There are many reports about its toxic effects to human 11 , phytoplankton 12 , aquatic animals 13 , and soil bacterial communities 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These interactions resulted in the formation of more extractable and less bound residues of 14 C‐metsulfuron‐methyl in high‐pH soils and less extractable and more bound residues in low‐pH soils. In addition, the anionic species of sulfonylurea herbicides were highly soluble in water and degraded at a slow rate in alkaline soils, which may significantly increase the potential for leaching (Sarmah et al, 2000; Delgado‐Moreno et al, 2007).…”
Section: Resultsmentioning
confidence: 99%